DAMPAK PROGRAM KELUARGA BERENCANA DAN PARTISIPASI KERJA PEREMPUAN TERHADAP KESEJAHTERAAN KELUARGA - Herlina, Herlina (Pascasarjana Universitas Halu Oleo, 2016)
This study aims to (1) analyze whether family planning program and women`s work participation simultaneously have any significant effect on the welfare of the families that are participating in the program at the sub district of Ranomeeto in South Konawe regency ; 2) analyze whether Family planning program has any significant effect on the welfare of the families that are participating in the program at the sub district of Ranomeeto in South Konawe Regency ; 3) analyze whether Women`s work participation have any significant effect on the welfare of the families that are participating in the program at the sub district of Ranomeeto in South Konawe regency. The object of this study are 2170 married couples who are participating as acceptors of Family planning program in the sub district of Ranomeeto. Samples are 96 people who are selected using the method Proportianate Stratified Random Sampling( a technique of sampling used if the population are heterogeneous and stratified proportional). Multiple linear analysis is performed to analyze the data. Result of the study show that 1). The family planning program and Women`s work participation that are run at the sub district of Ranomeeto in South Konawe regency have been able to improve the welfare of the families that are participating in the program and the program are also enhanced by a high level of work participation by women, particularly in relation to the big number of family members that must be supported ;2) Women`s work participation variable has a more dominant effect on the variable of family welfare than does the family participation program variable ; 3) The effect of Family planning program and women`s work participation variables on the variable of family welfare is 44,9% whereas the remaining 55,1% is affected by other variables that are not investigated by this study. Keywords: Family Planning Program, Women`s work participation, Family Welfare.